Archetypal criticism : the notion of monomania overturns the hero’s journey - Ahmad Muhyiddin Yusof,; Noraileen Ibrahim,; Nur Azmina Mohd Zamani,; Mohd Muzhafar Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Research have presented a broad overview concerning the notion of Archetypes. While previous studies equate the significance of Archetypes in recurring nature and familiarization of literary elements, the ways in which Archetypes ‘find’ cracks-in the stories are perpetually relegated. The relative significance of Archetypes, by taking into consideration works of novels, expose the gap between the oscillation of ‘departure’ and ‘conclusion.’ This study attempts to explore the many ways in which monomania is preserved, contested, and how monomania creates an ‘unstable alliance’ between characters and plots. Specifically, the notion of monomania is used to destabilize Archetypal Hero’s journey. First, the study sheds light on the Archetypal Hero character, named Heathcliff, in Wuthering Heights (1847) by Emily Bronte. Second, monomania is used as a lens to examine one of the central characters, Captain Ahab in Moby Dick (1851) by Herman Melville. By focusing on the concept of Archetypal Hero’s Journey, the influence of monomaniac is brought to the centre of discussion. As such, the destabilisation of plots and characters is described in its vibrancy through the lens of monomaniac.